PLACING LOCAL CULTURAL CONTENT INTO EFL TEACHING IN INDONESIA’S SCHOOLS - Fekry Nur (Universitas Negeri Padang, 2013)
English as a foreign language teaching (EFLT) in Indonesia could not yet enable high school graduate communicate intelligibly. Placing local cultural content into curriculum English for Indonesia’s schools shall improve EFLT for a better result, since it would raise the students cross cultural awareness. Local cultural content is the learners’ background of cultural values that influence their “what to say and how to say” on communication as a whole. English language learners in Indonesia are taught by or with model teachers from its locality. Hence, it is un-avoidable for the class (both teachers and students) to refer back to their local culture and values in their efforts to develop their transitional English. While it is hard to deny that a mere English cultural content in the EFLT contributed a lot to learners’ un-intelligible English and miss-communication, which may be caused by ‘broken culture’. I am proposing that local culture become issues in the EFL teaching content, and it should be intertwined with English culture, to foster a better understanding. But, the class must remain EFLT’s, not dangling to cultural study. In the end, students learning in EFLT classes will become aware that they are communicating in English language inter-culturally.